Understanding the Water Resources of a Small Rural Community: Citizen Science in Cascabel, Arizona. (19th September 2018) - Eastoe, Christopher J.; Clark, Barbara
Abstract: Cascabel residents have cooperated in assembling and discussing a dataset addressing community concerns about groundwater quality and sustainability of water supply in their reach of the semi‐arid San Pedro Valley. Most of the groundwater is drawn from Holocene sediments underlying the pre‐entrenchment floodplain of the San Pedro River and similar sediments in major tributaries. Stable O and H isotopes distinguish two main floodplain aquifers: A, containing groundwater derived from the Valley flanks, and B, containing groundwater labeled by the presence of ancient water from a hot‐spring system. In aquifer A, unpalatable groundwater containing dissolved ferrous iron and hydrogen sulfide is associated with clay containing buried wetland sediments that supply nutrients for microbial reduction of iron and sulfate. In aquifer B, groundwater is palatable, and static water levels at three locations have generally declined since the early 1990s, probably as a result of natural drainage in the upgradient part of the aquifer. Most groundwater from both aquifers contains measurable tritium, indicating vulnerability to multi‐decadal drought.